Electronic structures of the MoS2/TiO2 (anatase) heterojunction: influence of physical and chemical modifications at the 2D- or 1D-interfaces. Issue 4 (14th January 2022) - Favre, Rémi; Raybaud, Pascal; Le Bahers, Tangui
Abstract : The type of heterojunction (I, II, or Z-scheme) is tuned by the nature (2D-physical or 1D-chemical) of the interaction between MoS2 and TiO2 surface. Abstract : To tackle the challenge of CO2 photoreduction, semiconducting layered transition metal dichalcogenides like MoS2 have attracted much attention due to their tunable 2D nano-structures. By using advanced periodic density functional theory calculations (HSE06 functional), we provide a systematic quantification of the optoelectronic properties of various interfacial heterostructures composed of 2H-MoS2 and anatase TiO2 . We systematically determine the band gaps, and conduction band (CB) and valence band (VB) positions to figure out the nature of the heterojunction. Two main surface orientations of anatase TiO2 particles, (101) and (001), are considered with 2D-MoS2 nanosheets or nanoribbons forming either a 2D physical (van der Waals) or through a 1D chemical interface. The possibility to chemically modify the MoS2 /TiO2 interface, either by sulfidation or hydration, and its effect on the electronic structure are deeply investigated. These modifications in the heterostructure lead to important changes in the electronic properties and charge transfer between the two materials which impact both photon absorption properties and charge carrier dynamics suspected to influence in turn the photocatalytic activity. While a type I hetrojunction is found for the 1D chemical interface, a type II heterojunction with appropriate CB/VB positions for CO2 reduction and H2 O oxidation is identified for the 2D physical interface which could lead to the targeted Z-scheme mechanism with strong potential interest in photocatalysis applications.